Conception of yeast microbial desalination cell: applications to dye wastewater treatment and lead removal. Issue 3 (4th March 2021) - Yahiaoui, Chahinez; Kameche, Mostefa; Innocent, Christophe; Khenifi, Aicha
Abstract: Commercial textiles such as Decolor Stop (Eau Écarlate, France) were characterized, and their ability for adsorbing the dyes Congo red and methylene blue in an aqueous solution was investigated. The adsorption steps of equilibrium time and velocity for both dyes in textile commercial were determined. To describe adsorption mechanisms of Congo red and methylene blue, the kinetic adsorption data were treated with pseudo-first order and pseudo-second order. The experimental data of isotherms adsorption were examined using the Langmuir and Freundlich models, showing more affinity of material toward Congo red. Besides, an attempt toward biological regeneration of polluted textile was undertaken by integrating a bacterial biofilm into the process. In effect, the polluted textile was therefore regenerated by yeast microbial fuel cell in which it was consumed and used as a mediator for oxidizing the organic matter available. As a result, the produced electrons were transferred from the substrate (organic matter) to the anode via the dye, giving rise to the value of generated electromotive force. Then, the bio-energy harvested from this microbial fuel cell was exploited for removal of traces of lead contained in diluted aqueous solution. Accordingly, two processes were used: microbial desalination cell and conventional electro-dialysis for comparison. Although the desalination rates of the two processes were relatively close to each other, the electro-dialysis required some energy to spend for imposing the current, while in microbial desalination cell, the biological system provided the energy for removing traces of lead.